2002
DOI: 10.1242/jcs.00152
|View full text |Cite
|
Sign up to set email alerts
|

Wnt regulation of chondrocyte differentiation

Abstract: The Wnt family of growth factors are important regulators of several developmental processes including skeletogenesis. To further investigate the role of Wnts we analysed their expression in the developing chick limb and performed functional analyses in vivo and in vitro. We found that Wnt5b and Wnt11 are restricted within the prehypertrophic chondrocytes of the cartilage elements, Wnt5a is found in the joints and perichondrium, while Wnt4 is expressed in the developing joints and, in some bones, a subset of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
212
1
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(228 citation statements)
references
References 47 publications
9
212
1
6
Order By: Relevance
“…This Wnt is first expressed in cartilage anlagen and expression shifts to perichondrium with further development (16,19). Deletion of the Wnt-5a gene in mice causes a phenotype quite similar to that seen in CA-LEF transgenic mice here (17).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…This Wnt is first expressed in cartilage anlagen and expression shifts to perichondrium with further development (16,19). Deletion of the Wnt-5a gene in mice causes a phenotype quite similar to that seen in CA-LEF transgenic mice here (17).…”
Section: Resultsmentioning
confidence: 53%
“…Wnt-3a was found to share similar expression patterns and possibly similar roles (14). Subsequent studies indicated that Wnt-1, -4, and -7a exert inhibitory influences on differentiation of mesenchymal cells into chondrocytes, whereas Wnt-5a and -5b stimulate it (15,16). Wnt-5a and Wnt-5b were also shown to have strong influences on skeletogenesis in chick and mouse embryos (17)(18)(19).…”
mentioning
confidence: 99%
“…Growth factors of the Wnt family are also known to activate Rho GTPases, in addition to other signaling pathways (39,89,90). Several Wnt proteins control chondrocyte proliferation and differentiation (91,92). Among these, Wnt5b has been shown to stimulate chondrocyte proliferation in vivo (73), suggesting that these activities could be mediated by RhoA/ROCK.…”
Section: Discussionmentioning
confidence: 99%
“…A number of signaling pathways have been implicated in the regulation of chondrogenic differentiation and hypertrophy including Sox9, parathyroid hormone-related peptide, Indian hedgehog, bone morphogenetic protein, transforming growth factor-β, and the Wnt signaling pathways [33]. The effects of Wnt signaling on chondrogenesis are complex, as results indicate both stimulation and inhibition of chondrogenesis [34][35][36][37]. This suggests that the regulation by Wnt signaling may depend on the context of the cell or stage of differentiation ( Figure 2).…”
Section: Wnt Signaling In Chondrogenesismentioning
confidence: 99%